1991
DOI: 10.1139/b91-203
|View full text |Cite
|
Sign up to set email alerts
|

Leaf demography and decline of Panicum racemosum populations in coastal foredunes of southern Brazil

Abstract: We studied the effect of nutrient status and sand movement on the population biology of Panicum racemosum Spreng. over a 5-year period (1982–1986) on mobile, semifixed and fixed coastal foredune habitats in southern Brazil. The soils were deficient in nitrate, phosphate, and potassium (<0.5, 0.2–1.2, and 3–5 mg/kg, respectively) in all habitats, and a gradient of decreasing availability existed from the mobile to the fixed dunes. Half-lives of leaves were shorter in the fixed dune as compared with the mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
8

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 2 publications
0
14
0
8
Order By: Relevance
“…Large, rapidly growing plants are associated with sand containing macroalgal litter, whereas small stunted plants are found on foredunes above the limit of tidal inundation. Probably the small mass of Cakile seeds from southern Brazil reflects a low nutrient status (Costa et al 1991, Cordazzo 1994, because this population occurs not in a strandline habitat, but in the more stable conditions encountered at the base of foredunes (Seeliger 1992) where competition for nutrient may occur with the perennial grass Panicum racemosum (Beauv.) Spreng.…”
Section: Discussionmentioning
confidence: 99%
“…Large, rapidly growing plants are associated with sand containing macroalgal litter, whereas small stunted plants are found on foredunes above the limit of tidal inundation. Probably the small mass of Cakile seeds from southern Brazil reflects a low nutrient status (Costa et al 1991, Cordazzo 1994, because this population occurs not in a strandline habitat, but in the more stable conditions encountered at the base of foredunes (Seeliger 1992) where competition for nutrient may occur with the perennial grass Panicum racemosum (Beauv.) Spreng.…”
Section: Discussionmentioning
confidence: 99%
“…Na área B, as espécies que se destacaram foram Panicum racemosum e Sporobolus virginicus, características da comunidade psamófila-reptante (Henriques et al 1986). Panicum racemosum tem ocorrência significativa em outras regiões do litoral brasileiro, principalmente em áreas próximas ao mar e com muita movimentação de areia (Pfadenhauer 1978;Costa et al 1984;Costa et al 1991) o que justamente caracteriza a área B. Segundo Costa et al (1996), o acréscimo de areia, oriundo de ação eólica ou antrópica, controla a germinação das sementes desta espécie e o estabelecimento da plântula, daí a preferência por estas áreas. Devido a esta característica, esta espécie age como pioneira, formadora e fixadora de dunas (Dansereau 1947;Henriques et al 1984;Cordazzo & Costa 1989;Cordazzo & Seeliger 1993).…”
Section: Discussionunclassified
“…On the other hand, later-germinating seedlings can suffer increased mortality and/or reduced growth (Zimmerman & Weis, 1983). In the southern Brazilian sand-dune environment, the supply of nutrients is limited (Costa et al, 1991) and early germinating seedling probably have a better chance of growth and establishment at locations where seedling density is high, like depressions between dune ridges. The three species studied also showed that seedlings from large seeds present significantly higher elongation in darkness than do those from small seeds (Cordazzo, 1994).…”
Section: Tablementioning
confidence: 99%